The Influence of Environmental Consciousness, Green Lifestyle, Influencer Credibility, and Social Media Engagement on Purchase Intention of Slow Fashion Products on the TikTok Application among Generation Z - Fajar ASHSIDIK; Setyo Ferry WIBOWO; Andi Muhammad SADAT (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2025)
This study analyzes the influence of environmental awareness, green lifestyle, influencer credibility, and social media engagement on slow fashion purchase intentions among Generation Z on TikTok. The massive fast fashion industry contributes to environmental problems, with significant clothing waste in Indonesia. Slow fashion offers sustainable solutions, but its implementation remains limited. Generation Z, as primary consumers of fast fashion and active TikTok users, has the potential to be a driver of change. Using quantitative methods on 200 Generation Z respondents in Greater Jakarta (Jabodetabek) who were exposed to slow fashion content on TikTok, the results show that environmental awareness positively influences slow fashion purchase intentions and green lifestyle. Influencer credibility increases social media engagement, which in turn influences green lifestyle and purchase intentions. However, green lifestyle does not directly influence slow fashion purchase intentions, as Generation Z may prioritize mindful clothing consumption (e.g., capsule wardrobes) over simply purchasing new products. Influencer credibility also does not directly influence purchase intentions, possibly due to skepticism of promotional content or a lack of influencer expertise in sustainable fashion. In conclusion, increasing environmental awareness and engaging social media engagement are crucial to driving slow fashion purchase intentions among Generation Z. Marketing strategies must go beyond influencer credibility alone to effectively drive purchases. This research provides valuable insights into understanding consumer behavior and desires.